Life cycle assessment parameters adaptation for Brazilian electricity production - Coelho, Carla (My University, 2009)
Electricity is a major concern in the life cycle assessment (LCA) of most products since it is a required input for production of almost all goods. The largest life cycle inventory (LCI) databases contain, mainly, data for Europe and North America, while goods are produced in several other locations. Electricity generation in Brazil was chosen as a case study. Instead of making a totally new inventory this study started from an existing dataset for electricity mix, available on the database of ecoinvent (which has the composition of the mix according to Brazilian generation, i.e. the amount of electricity generation from each electricity source). The first step was to update the amount of each type of electricity contributing for the current mix, according to the latest available data. The impact assessment was carried out using three methods: EPS 2000, eco-indicator 99 and the single use method IPCC-GWP 100a. The results provided the base to identify which were the most contributing electricity types to certain categories. The impact assessment indicated the methane emissions from hydropower reservoirs, the bagasse electricity generation carcinogens impacts to be relevant parameters to be investigated further. As well the type of coal mining was altered to open cast mine in order to be more representative of the Brazilian coal mining reality. Difficulties were faced when attempting to select the most appropriate value for methane emissions in tropical reservoirs. In regards to the greenhouse gas emissions the greatest impact variation was a result of the usage of the worse and average cases, as well as alteration of characterization factors. Another factor highly relevant for the LCA impact of hydro power is the energy density, which had a significant variation from different hydropower plants in Brazil. For bagasse generation outdated data could have a significant impact in certain categories, although due to the small contribution to the Brazilian mix the difference impact becomes much less significant. The alteration of the type of mining did not result in a difference when compared to underground mining.
Keywords: Miljöteknik; Environmental engineering